Home isolation deaths during the third wave of COVID-19 pandemic in Kerala: a descriptive study - Jithesh, Veetilakath; Ravindran, Rekha Meleparambil; Retnakala, Anjali Krishnan; Raheela, Ameena Subair; Kumari, Divya Indira; Nair, Chinnu Rema; Nair Lathika, Aswathy Kuttappan; Das, Hiran Mohan (International Journal Of Community Medicine And Public Health, 2022)
Background: The state government directed its efforts to mitigate transmission of new variant SARS-CoV-2 called Omicron. This study aimed to describe pathways and characteristics of home isolation (HI) deaths reported in Kerala during third wave of pandemic. Methods: The study adopted retrospective cross sectional descriptive approach, conducted among HI patients who died from January15th to February 15th 2022. The sociodemographic, clinical characteristics and the events that happened prior to deaths were collected through verbal autopsy. The state declared 106 HI deaths with case fatality rate of 2% (95% CI 1.5-2.50%). After screening, 70 HI deaths (54 home deaths and 16 in-transit deaths) were studied. Results: Majority were home deaths (84.29%) followed by in-transit deaths (15.71%). Mortality was higher among older persons (94.28%), females (51.42%), unemployed (68.57%) and patients in rural community. Majority had comorbidities (80%) mainly diabetes mellitus (55.35%). The median interval from symptom onset to death was five days (IQR) 4-8) and that from diagnosis to death was four days (IQR 2-8). Majority reported red flag signs (83.07%) commonly breathlessness (83.34%). Most of the deceased (80%) did not monitor oxygen saturation. The study identified four patterns of HI deaths, primarily due to delay in identification of red flag signs and hospitalization. Conclusions: Non-compliance to oxygen monitoring, slow response towards red flag signs and delay in hospitalization were the main reasons for HI deaths. Stringent monitoring mechanism for HI patients at primary health care and meteoric referral strategy can prevent fatalities in future.